Method for directly preparing iron-magnesium doped ternary positive electrode material from manganese purification slag
By using manganese dioxide and impurity iron to carry out acid leaching and co-precipitation reactions in manganese purification slag, an iron-magnesium-doped ternary cathode material with good circulation performance was prepared, and manganese purification with different impurity content in the prior art was solved. The recycling and utilization of slag is difficult, which achieves efficient recycling of resources and high-performance production of ternary cathode materials.
Patent Information
- Application Number
- CN202411405835.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-14
AI Technical Summary
The prior art is difficult to effectively use manganese purification slag with different impurity content to prepare ternary cathode materials, especially inadequate recycling and utilization of iron elements, resulting in waste of resources and high production costs.
Through leaching, calcium removal, metal molar ratio adjustment, precursor preparation and calcining processes, manganese dioxide as an oxidant is used to dissolve the metal components in the manganese purified slag under acidic conditions, and combine manganese ore and impurity iron to control the sulfate leaching liquid. The molar ratio of nickel-cobalt-manganese-mafen was carried out, and a co-precipitation reaction was carried out to prepare a ferromagnesium-doped ternary cathode material with good cycle performance.
It realizes efficient resource recycling and utilization of manganese slag, shortens the process flow, improves the material's cycle performance and charge-discharge specific capacity, maintains high capacity stability, and avoids surface modification of the precursor of the ternary positive electrode material deal with.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrometallurgy and material preparation and production, and specifically relates to a method for directly preparing an iron-magnesium doped ternary positive electrode material from manganese purified slag. Background Art
[0002] In manganese production enterprises, every ton of manganese metal produced will produce 8 to 10 tons of slag, and manganese purification slag is one of the main slags. The main components are sulfides such as manganese, cobalt, nickel, iron, calcium, and magnesium. The manganese content is about 10% to 15%, nickel 0.3% to 1.0%, cobalt 0.3% to 1.0%, and calcium, magnesium, and iron are the main impurities. The cobalt and nickel content in the slag is higher than the metal content of cobalt and nickel in common cobalt-nickel minerals. The amount is large, and the rapid development of the global lithium battery industry has caused a large gap in the raw materials of cobalt and nickel in nickel-cobalt-manganese ternary positive electrode materials, and the price is getting higher and higher. If the valuable metals in manganese purification slag can be fully utilized to directly prepare ternary positive electrode materials, it can not only solve the environmental problems that may be caused by slag, but also realize the high-value utilization of slag, reduce the production cost of ternary positive electrode materials, and kill several birds with one stone, but there are still some key technologies that need to be broken through urgently.
[0003] We have found the following patents on the preparation of doped ternary cathode materials from waste slag:
[0004] 1. Application number: 202110002935.3, invention name: A method for regenerating a ternary precursor using nickel-cobalt-manganese slag. The invention mixes nickel-cobalt-manganese slag, water and a reducing agent, adjusts the resulting mixed solution to alkalinity, and then mixes it with an ammonium salt to obtain a mixed liquid; the mixed liquid is subjected to a hydrothermal reaction to obtain a ternary precursor. The invention mixes nickel-cobalt-manganese slag and a reducing agent for a hydrothermal reaction. Under the action of the reducing agent, the metal oxides in the nickel-cobalt-manganese slag are reduced to the corresponding +2-valent metal hydroxides. The invention controls the morphology and particle size of the product by adjusting the pH value, adding ammonium salts, and controlling the hydrothermal reaction temperature, and ultimately restores the morphology and electrochemical properties of the original ternary precursor to the resulting product. The method provided by the invention directly reduces nickel-cobalt-manganese slag to a ternary precursor, which can achieve the recycling of waste ternary positive electrode materials and has great application prospects. However, this invention is about the recycling of waste nickel-cobalt-manganese-oxide lithium ternary positive electrode materials. The main elements in the waste slag components studied are nickel, cobalt, manganese and oxygen, and do not contain elements such as iron, calcium and magnesium. Therefore, it has no reference value for the recycling process of manganese purification slag with different impurities and contents.
[0005] 2. Application number: 202110686506.2, invention name: A method for preparing a ternary positive electrode material using manganese, cobalt and nickel-containing waste slag, which is carried out according to the following steps: (1) crushing and screening; (2) oxidative leaching; (3) decalcification; (4) optimizing the ratio of manganese, cobalt, nickel and magnesium; (5) preparation of a magnesium ion-doped manganese, cobalt and nickel ternary positive electrode material precursor; (6) preparation of a ternary positive electrode material; (7) surface modification: dispersing the ternary positive electrode material in water, taking the manganese, cobalt, nickel and magnesium rich solution after decalcification in step (3) and ammonium fluoride as modifiers in a certain mass ratio, and performing surface modification on the ternary positive electrode material. After the modification, the finished product is obtained by post-treatment. The method is simple and feasible, and can achieve the leaching of manganese-cobalt-nickel-magnesium-containing waste residues, filter and remove impurities from the filtrate, and directly prepare a magnesium ion-doped manganese-cobalt-nickel ternary positive electrode material precursor, and prepare a ternary positive electrode material, which can not only achieve comprehensive utilization of waste residues, but also improve the ionic conductivity of the product, inhibit the increase of electrochemical impedance, and improve the cycle performance. The impurity iron element has not yet been effectively recycled in this method, so it can only be oxidized during leaching to precipitate the iron element; in addition, it is necessary to use the decalcified manganese-cobalt-nickel-magnesium solution and ammonium fluoride as surface modifiers to modify the surface of the calcined ternary positive electrode material in order to achieve the so-called cycle performance, and there is a problem of a long processing flow.
[0006] 3. Application number: 202310305598.4, invention name: A method for preparing copper-magnesium doped lithium battery 811 positive electrode material from nickel-cobalt slag in Xinjiang Uygur Autonomous Region, mainly comprising the following steps: (1) Washing and filtering the nickel-cobalt slag in Xinjiang Uygur Autonomous Region with water to remove soluble impurities. (2) Reduction acid leaching Under heating and stirring conditions, add a certain ratio of concentrated sulfuric acid and hydrogen peroxide to the slag, filter, and obtain a mixed solution 1. (3) Extraction and impurity removal At a certain pH, use an extractant to extract the impurity metal ions in the mixed solution 1 to obtain a mixed solution 2. (4) Liquid phase mixing Add nickel sulfate and manganese sulfate to the mixed solution 2 in a certain ratio, stir evenly to obtain a mixed solution 3. (5) Coprecipitation: Using the mixed solution 3 as the raw material, a ternary material precursor doped with copper and magnesium in situ is prepared in a reactor by a coprecipitation process: nitrogen is introduced under heating and stirring conditions, and ammonia water is used as the base liquid. The mixed solution 3 and sodium hydroxide solution are added simultaneously. After a period of reaction, stirring is stopped, and the mixture is aged for a period of time. Then, the obtained wet ternary material precursor is filtered, washed, dried and ground to obtain powder 4. (6) Calcination: The powder 4 is mixed and ground evenly with lithium hydroxide, and then placed in a tubular furnace and calcined with oxygen to obtain a ternary material doped with copper and magnesium. However, the nickel-cobalt slag material of the invention mainly contains nickel, cobalt, manganese, copper, magnesium, barium, iron, zinc and aluminum as the main elements. Therefore, it has no reference value for the recycling process of manganese purification slag with different impurities and contents.
[0007] 4. Application number: 202410209120.6, invention name: A processing technology for recovering cobalt-manganese waste slag to prepare ternary materials, comprising the following steps: pre-treating the cobalt-manganese waste slag to obtain recycled metal powder; mixing the recycled metal powder and the leaching solution evenly, raising the temperature of the leaching solution to 60-80°C, stirring for 3-4 hours, and post-treating to obtain a leaching solution and leaching slag; re-treating the leaching solution to obtain recycled metal; mixing the recycled metal with a sulfuric acid solution to obtain a metal mixture; using an atomic emission spectrometer to detect the content of cobalt, manganese and nickel ions in the metal mixture, adding a nickel source, a cobalt source, a manganese source and a chelating agent to the metal mixture to obtain a precursor solution, adding a 20wt% sodium hydroxide solution to the precursor solution, adjusting the system pH to 11-13, stirring at room temperature for 30-50min, and post-treating to obtain a ternary precursor; adding lithium carbonate and additives to the ternary precursor for ball milling and mixing, and calcining to obtain a ternary positive electrode material. However, this invention is about the recovery of important elements such as cobalt and manganese in ternary materials, so it has no reference value for the recycling process of manganese purification slag with different impurities and contents. Summary of the invention
[0008] The purpose of the present invention is to solve the above technical problems and provide a method for directly preparing iron-magnesium doped ternary positive electrode materials from manganese purified slag, which has a short process flow, good product cycle performance and can achieve efficient resource recycling.
[0009] To achieve the above-mentioned purpose, the technical solution of the present invention is:
[0010] A method for directly preparing an iron-magnesium doped ternary positive electrode material from manganese purified slag, comprising leaching, decalcification, metal molar ratio adjustment, precursor preparation and calcination of manganese purified slag whose main components are nickel, cobalt, manganese, magnesium, iron and calcium, to obtain a doped ternary positive electrode material;
[0011] The leaching is to add an excessive amount of manganese dioxide-rich material to the manganese purification slag, mix and crush to obtain a mixed slag; then add dilute sulfuric acid to heat the mixed slag under acidic conditions to leach, and obtain a sulfate leachate containing nickel, cobalt, manganese, magnesium, iron and calcium. In the present invention, manganese dioxide is used as an oxidant to dissolve the metal components in the manganese purification slag, and the impurity iron in the pyrolusite and manganese purification slag is used to control sulfur and leach metals such as nickel, cobalt, manganese, magnesium, iron and calcium. The principle is:
[0012] MnO2+2Fe 2+ +4H + =Mn 2+ +2Fe 3+ +2H2O;
[0013] MS+4H + =M 2+ +H2S(M=Ni, Co, Mn, Mg, Fe, Ca)
[0014] Fe 3+ +H2S=Fe 2+ +S↓+2H + ;
[0015] Under acidic conditions, MnO2 in pyrolusite oxidizes Fe 2+ Fe 3+ At the same time, the metal sulfide solution acidifies to generate H2S, which immediately reacts with Fe 3+ The reaction generates sulfur which precipitates, while the excess pyrolusite MnO2 keeps the iron in the solution trivalent.
[0016] The calcium removal is performed by adding an organic phosphate extractant to the sulfate leaching solution under acidic conditions to extract the sulfate leaching solution, thereby obtaining a sulfate purification solution containing nickel, cobalt, manganese, magnesium and iron from which most of the calcium ions have been removed;
[0017] The metal molar ratio adjustment is based on the nickel, cobalt, manganese, magnesium and iron content in the sulfate purification solution, and the nickel, cobalt, magnesium and iron salt compounds are supplemented to make the molar ratio of nickel, cobalt, manganese, magnesium and iron in the solution reach (4.95-5.05):(1.95-2.05):(2.95-3.05):(0.01-0.04):(0.01-0.04);
[0018] The precursor is prepared by adding concentrated ammonia water to the sulfate purification liquid with a good molar ratio, heating, then adding sodium hydroxide to maintain alkaline conditions, and introducing oxygen to perform a co-precipitation reaction. The addition of oxygen in the reaction is to ensure that manganese and iron are in a high-valent state. The obtained precipitate is subsequently treated to obtain a doped ternary positive electrode material precursor.
[0019] The calcination is to mix the doped ternary cathode material precursor and lithium hydroxide, and then perform low-temperature roasting and high-temperature calcination to obtain the doped ternary cathode material.
[0020] As a further technical solution, the mass ratio of the manganese purification slag to the substance rich in manganese dioxide is 1:(10-14), and the substance rich in manganese dioxide in this ratio is added in excess; the concentration of the dilute sulfuric acid is 90g / L-110g / L, the liquid-solid ratio of the dilute sulfuric acid to the mixed slag is (6-9)mL:1g, the temperature of the heating leaching is 70-90°C, the leaching time is 150-180min, and the particle size of the crushed material is 0.0374mm-0.0750mm.
[0021] As a further technical solution, the above-mentioned substance rich in manganese dioxide is pyrolusite.
[0022] As a further technical solution, in the above-mentioned calcium removal, the acidic condition is pH 1.0-2.0; the organic phosphate extractant is prepared by mixing P204 and sulfonated kerosene at a volume ratio of 10% to 30% of P204, and then adding sodium hydroxide for saponification, wherein the saponification rate is 10% to 30%, and the ratio of the organic phase to the sulfate leachate is (1 to 3):1.
[0023] As a further technical solution, in the above-mentioned nickel-cobalt-magnesium-iron salt compounds, the nickel salt is one or a mixture of nickel sulfate, nickel chloride, nickel acetate and nickel nitrate; the cobalt salt is one or a mixture of cobalt sulfate, cobalt chloride, cobalt acetate and cobalt nitrate; the magnesium salt is one or a mixture of magnesium sulfate, magnesium chloride and magnesium nitrate; and the iron salt is one or a mixture of ferric sulfate and ferric chloride.
[0024] As a further technical solution, in the above preparation of the precursor, the concentrated ammonia water is added to a concentration of 1 to 2 mol / L, the heating temperature is 50 to 70°C, the alkaline condition is pH 10 to 11.5, the concentration of sodium hydroxide is 1 to 1.5 mol / L, the flow rate of oxygen introduced is 1 to 5 L / min, and the coprecipitation reaction time is 30 to 60 min.
[0025] As a further technical solution, the above-mentioned subsequent treatment includes aging, washing, centrifugal separation, drying, ball milling and screening the precipitate.
[0026] As a further technical solution, in the subsequent treatment, the aging time is 60 to 120 minutes; the drying temperature is 100 to 105°C, and the drying time is 6 to 8 hours; the ball milling speed is 300 to 500 r / min, and the ball milling time is 3 to 6 hours; the sieving size is 0.0374 mm to 0.0750 mm.
[0027] As a further technical solution, the molar ratio of the above-mentioned doped ternary positive electrode material precursor and lithium hydroxide is 1: (1.05~1.1), the temperature of the low-temperature calcination is 350~500°C, and the time is 2~4h; the temperature of the high-temperature calcination is 800~900°C, and the calcination time is 10~16h.
[0028] As a further technical solution, the speed of the ball milling is 300-500 r / min, and the ball milling time is 3-6 h.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] 1. The present invention can realize efficient and comprehensive recycling and reuse of resources.
[0031] The core of the invention is to deeply analyze the manganese purification slag, thereby exploring the important role of iron in the preparation of ternary positive electrode materials. This breakthrough not only breaks the limitation of traditional recycling technology that must remove iron, but also opens up a new way to achieve more efficient, comprehensive recycling and reuse of resources.
[0032] 2. The process flow of the present invention is short and the material recycling performance is good.
[0033] The present invention utilizes impure metal ions of iron and magnesium to improve the stability of the crystal structure of the material. Through the reasonable proportion of nickel, cobalt, manganese, magnesium and iron elements, not only can these elements be efficiently recycled and reused, but also the material's first charge and discharge specific capacity reaches a high level of more than 153mAh / g. While maintaining the material's 100-week capacity retention rate of more than 98.0%, it can also avoid the modification of the surface of the ternary positive electrode material precursor, thereby achieving a short process flow and good material cycle performance. In addition, in the process from low rate to high rate, the average discharge specific capacity of the first 5 cycles decreases by only 10%-16%, showing good charge and discharge stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 is the X-ray diffraction analysis diagram of pyrolusite;
[0035] Figure 2 This is an X-ray diffraction analysis diagram of manganese purification slag;
[0036] Figure 3 is the X-ray diffraction analysis diagram of the slag after leaching;
[0037] Figure 4 This is an electron microscope scanning image of pyrolusite;
[0038] Figure 5 This is a scanning electron microscope image of manganese purification slag;
[0039] Figure 6 This is the electron microscope scanning image of the slag after leaching. DETAILED DESCRIPTION
[0040] The present invention is further described in detail below in conjunction with examples, but the implementation mode of the present invention is not limited to the scope represented by the examples.
[0041] The manganese purification slag in the embodiment of the present invention comes from a manganese production enterprise in Guangxi Zhuang Autonomous Region, and its main components are shown in Table 1.
[0042] Table 1 Main components of manganese purification slag
[0043]
[0044] Embodiment 1:
[0045] Mix the manganese purification slag and pyrolusite in a mass ratio of 1:10, crush, pass through a 0.0750mm sieve, and set aside. Weigh 100g of the above mixed slag, add 600mL of 90g / L dilute sulfuric acid in a reactor, heat to 80°C, stir and leach for 180min, filter, and obtain the leachate. Adjust the pH of the leachate to 2.0, add 600mL of P204 with a saponification rate of 10% as an extractant (P204 and sulfonated kerosene are pre-mixed at a volume ratio of 30% of P204) to extract calcium, retain the aqueous phase purification liquid, and recycle the organic phase. Use a plasma emission spectrometer to detect the content of nickel, cobalt, manganese, magnesium and iron, add additional nickel, cobalt, magnesium and iron sulfates, and adjust the filtrate nickel, cobalt, manganese, magnesium and iron to a certain molar ratio of 5.05:1.95:3.00:0.01:0.03. Obtain 600 mL of the above solution, transfer it to a reactor, add 46 mL of concentrated ammonia water, adjust the ammonia concentration to 1.0 mol / L, heat to 60°C, add 1.0 mol / L sodium hydroxide, control the pH value of the solution at 10, introduce oxygen at a flow rate of 2 L / min, and keep warm for 40 min. Stop introducing oxygen, age for 90 min, filter, wash, dry at 105°C for 8 h, ball mill at 400 r / min for 6 h, and pass through a 0.0750 mm sieve to obtain 84.9 g of a doped ternary positive electrode material precursor. The precursor metal content was detected by plasma emission spectrometer, 0.89 g of lithium hydroxide was added according to the molar ratio of precursor metal to lithium hydroxide = 1:1.07, and ball milled at 400 r / min for 6 h. The mixture was first calcined at 350°C for 4 h, then calcined at 800°C for 10 h, and ball milled at 400 r / min for 6 h to obtain 82.7 g of doped NCM523 ternary positive electrode material.
[0046] Embodiment 2:
[0047] Mix the manganese purification slag and pyrolusite in a mass ratio of 1:12, crush, pass through a 0.0374mm sieve, and set aside. Weigh 100g of the above mixed slag, add 700mL of 100g / L dilute sulfuric acid in a reactor, heat to 70°C, stir and leach for 170min, filter, and obtain the leachate. Adjust the pH of the leachate to 1.0, add 1050mL of P204 with a saponification rate of 20% as an extractant (P204 and sulfonated kerosene are pre-mixed at a volume ratio of 20% of P204) to extract calcium, retain the aqueous phase purification liquid, and recycle the organic phase. Use a plasma emission spectrometer to detect the content of manganese, cobalt, nickel, magnesium and iron, add nickel, cobalt, magnesium and iron sulfates, and adjust the filtrate nickel, cobalt, manganese, magnesium and iron to a certain molar ratio of 5.00:1.95:3.05:0.02:0.02. Obtain 600 mL of the above solution, transfer it to a reactor, add 69 mL of concentrated ammonia water, adjust the ammonia concentration to 1.5 mol / L, heat to 50°C, add 1.0 mol / L of sodium hydroxide, control the pH value of the solution at 11.5, introduce oxygen at a flow rate of 1 L / min, and keep warm for 30 min. Stop introducing oxygen, age for 120 min, filter, wash, dry at 105°C for 6 h, ball mill at 300 r / min for 6 h, and pass through a 0.0374 mm sieve to obtain 80.8 g of a doped ternary positive electrode material precursor. The precursor metal content was detected by plasma emission spectrometer, 0.86 g of lithium hydroxide was added according to the molar ratio of precursor metal to lithium hydroxide = 1:1.08, and ball milling was carried out at 300 r / min for 6 h. The mixture was first calcined at 400°C for 3 h, then calcined at 850°C for 12 h, and ball milling was carried out at 300 r / min for 6 h to obtain 79.5 g of doped NCM523 ternary positive electrode material.
[0048] Embodiment 3:
[0049] Mix the manganese purification slag and pyrolusite in a mass ratio of 1:13, crush, pass through a 0.0374mm sieve, and set aside. Weigh 100g of the above mixed slag, add 900mL of 110g / L dilute sulfuric acid in a reactor, heat to 90°C, stir and leach for 160min, filter, and obtain the leachate. Adjust the pH of the leachate to 1.5, add 450mL of P204 with a saponification rate of 30% as an extractant (P204 and sulfonated kerosene are pre-mixed at a volume ratio of 10% of P204) to extract calcium, retain the aqueous phase purification liquid, and recycle the organic phase. Use a plasma emission spectrometer to detect the content of manganese, cobalt, nickel, magnesium and iron, add nickel, cobalt, magnesium and iron sulfates, and adjust the filtrate nickel, cobalt, manganese, magnesium and iron to a certain molar ratio of 4.95:2.05:3.00:0.03:0.01. Obtain 600 mL of the above solution, transfer it to a reactor, add 92 mL of concentrated ammonia water, adjust the ammonia concentration to 2.0 mol / L, heat to 70°C, add 1.5 mol / L of sodium hydroxide, control the pH value of the solution at 10, introduce oxygen at a flow rate of 5 L / min, and keep warm for 50 min. Stop introducing oxygen, age for 100 min, filter, wash, dry at 105°C for 7 h, ball mill at 500 r / min for 4 h, and pass through a 0.0374 mm sieve to obtain 79.1 g of a doped ternary positive electrode material precursor. The precursor metal content was detected by plasma emission spectrometer, 0.85 g of lithium hydroxide was added according to the molar ratio of precursor metal to lithium hydroxide = 1:1.1, and ball milling was carried out at 500 r / min for 4 h. The mixture was first calcined at 500°C for 4 h, then calcined at 800°C for 16 h, and ball milling was carried out at 500 r / min for 4 h to obtain 79.2 g of doped NCM523 ternary positive electrode material.
[0050] Embodiment 4:
[0051] Mix the manganese purification slag and pyrolusite in a mass ratio of 1:14, crush, pass through a 0.0750mm sieve, and set aside. Weigh 100g of the above mixed slag, add 800mL of 90g / L dilute sulfuric acid in a reactor, heat to 80°C, stir and leach for 150min, filter, and obtain the leachate. Adjust the pH of the leachate to 1.0, add 800mL of P204 with a saponification rate of 15% as an extractant (P204 and sulfonated kerosene are pre-mixed at a volume ratio of 15% of P204) to extract calcium, retain the aqueous phase purification liquid, and recycle the organic phase. Use a plasma emission spectrometer to detect the content of manganese, cobalt, nickel, magnesium and iron, add nickel, cobalt, magnesium and iron sulfates, and adjust the filtrate nickel, cobalt, manganese, magnesium and iron to a certain molar ratio of 5.05:2.00:2.95:0.01:0.03. Obtain 600 mL of the above solution, transfer it to a reactor, add 69 mL of concentrated ammonia water, adjust the ammonia concentration to 1.5 mol / L, heat to 60°C, add 1.5 mol / L sodium hydroxide, control the pH value of the solution at 11, introduce oxygen at a flow rate of 4 L / min, and keep warm for 60 min. Stop introducing oxygen, age for 60 min, filter, wash, dry at 105°C for 8 h, ball mill at 400 r / min for 3 h, and pass through a 0.0750 mm sieve to obtain 77.9 g of a doped ternary positive electrode material precursor. The precursor metal content was detected by plasma emission spectrometer, 0.80 g of lithium hydroxide was added according to the molar ratio of precursor metal to lithium hydroxide = 1:1.05, and ball milling was carried out at 450 r / min for 5 h. The mixture was first calcined at 500°C for 2 h, then calcined at 900°C for 15 h, and ball milling was carried out at 450 r / min for 5 h to obtain 74.5 g of doped NCM523 ternary positive electrode material.
[0052] Comparative experiment
[0053] The sulfate purified solution after the calcium removal step in Example 1 was used as the basic solution for adjusting the molar ratio. The main metal contents of the sulfate purified solution are shown in Table 2:
[0054] Table 2
[0055]
[0056] Comparative Example 1: Based on the amount of manganese as 0.26 mol, nickel sulfate, cobalt sulfate and manganese sulfate were prepared into 600 mL solution according to the molar ratio of nickel, cobalt and manganese of 5.00:2.00:3.00, and the solution was transferred to a reactor. 46 mL of concentrated ammonia water was added to adjust the ammonia concentration to 1.0 mol / L, heated to 60°C, 1.0 mol / L of sodium hydroxide was added, the pH value of the solution was controlled at 10, oxygen was introduced at a flow rate of 2 L / min, the insulation time was 40 min, the introduction of oxygen was stopped, the solution was aged for 90 min, filtered, washed, dried at 105°C for 8 h, ball milled at 400 r / min for 6 h, and passed through a 0.0750 mm sieve to obtain a sample of Comparative Example 1.
[0057] Comparative Example 2: Based on the amount of manganese as 0.26 mol, nickel sulfate, cobalt sulfate and manganese sulfate were configured into 600 mL solution according to the molar ratio of nickel, cobalt, manganese and magnesium of 5.00:2.00:2.98:0.02, and the solution was transferred to a reactor. 46 mL of concentrated ammonia water was added, and the ammonia concentration was adjusted to 1.0 mol / L. The solution was heated to 60°C, 1.0 mol / L of sodium hydroxide was added, the pH value of the solution was controlled at 10, oxygen was introduced at a flow rate of 2 L / min, and the insulation time was 40 min. The oxygen was stopped, aged for 90 min, filtered, washed, dried at 105°C for 8 h, ball milled at 400 r / min for 6 h, and sieved through a 0.0750 mm sieve to obtain a sample of Comparative Example 2.
[0058] Comparative Example 3: Based on the amount of manganese as 0.26 mol, nickel sulfate, cobalt sulfate and manganese sulfate were configured into 600 mL solution according to the molar ratio of nickel, cobalt, manganese and iron of 5.00:2.00:2.98:0.02, and the solution was transferred to a reactor. 46 mL of concentrated ammonia water was added, and the ammonia concentration was adjusted to 1.0 mol / L. The solution was heated to 60°C, 1.0 mol / L of sodium hydroxide was added, the pH value of the solution was controlled at 10, oxygen was introduced at a flow rate of 2 L / min, and the insulation time was 40 min. The oxygen was stopped, aged for 90 min, filtered, washed, dried at 105°C for 8 h, ball milled at 400 r / min for 6 h, and sieved through a 0.0750 mm sieve to obtain a sample of Comparative Example 3.
[0059] The products obtained in Examples 1 to 4 and Comparative Examples 1 to 3 were tested for the first charge-discharge capacity and 100 cycles under 1C conditions using a CT-4008T battery testing system. The results are shown in Table 3:
[0060] Table 3 Capacity comparison between the embodiment and the comparative example
[0061]
[0062] From Table 3 we can see:
[0063] (1) The doped NCM523 ternary positive electrode material prepared from manganese purification slag in the present invention can achieve an initial charge and discharge specific capacity of more than 150 mAh / g, and a capacity retention rate of more than 98.0% for 100 weeks, and has good cycle performance.
[0064] (2) The doped NCM523 ternary positive electrode material prepared from manganese purification slag in the present invention has a better charge-discharge specific capacity and capacity retention rate than the undoped magnesium-iron material of comparative example 1, the doped magnesium material of comparative example 2, and the doped iron material of comparative example 3.
[0065] The products obtained in Examples 1 to 4 and Comparative Examples 1 to 3 were subjected to 5 cycles of charge and discharge cycle tests at 0.5C, 1C, 2C, and 5C rates, respectively, using a CT-4008T battery testing system. The average discharge specific capacity results of the first 5 cycles at different rates are shown in Table 4:
[0066] Table 4 Rate performance comparison between the embodiment and the comparative example
[0067]
[0068]
[0069] It can be seen from Table 4 that the doped NCM523 ternary positive electrode material prepared from manganese purification slag in the present invention, after the same discharge from low rate to high rate, the discharge specific capacity of the doped NCM523 ternary positive electrode material prepared by the present invention decreases less than the discharge specific capacity of the undoped or single-doped material, indicating that the stability during charge and discharge is relatively excellent.
[0070] The above embodiments are only specific examples for further describing the purpose, technical solutions and beneficial effects of the present invention, and the present invention is not limited thereto. Any modification, equivalent replacement, improvement, etc. made within the scope disclosed by the present invention are included in the protection scope of the present invention.
Claims
1. A method for directly preparing iron-magnesium doped ternary positive electrode materials from manganese purified slag, characterized in that: The method is to obtain a doped ternary positive electrode material by leaching, decalcifying, adjusting the metal molar ratio, preparing a precursor and calcining the manganese purified slag whose main components are nickel, cobalt, manganese, magnesium, iron and calcium; The leaching is to add an excessive amount of manganese dioxide-rich material to the manganese purification slag, mix, and crush to obtain a mixed slag; then add dilute sulfuric acid to heat and leach the mixed slag under acidic conditions to obtain a sulfate leachate containing nickel, cobalt, manganese, magnesium, iron, and calcium; The calcium removal is performed by adding an organic phosphate extractant to the sulfate leaching solution under acidic conditions to extract the sulfate leaching solution to obtain a sulfate purified solution; The metal molar ratio adjustment is based on the nickel, cobalt, manganese, magnesium and iron content in the sulfate purification solution, and the nickel, cobalt, magnesium and iron salt compounds are supplemented to make the molar ratio of nickel, cobalt, manganese, magnesium and iron in the solution reach (4.95-5.05): (1.95-2.05): (2.95-3.05): (0.01-0.04): (0.01-0.04); The precursor is prepared by adding concentrated ammonia water to the sulfate purification liquid with a good molar ratio, heating, then adding sodium hydroxide to maintain alkaline conditions, and introducing oxygen to perform a co-precipitation reaction, and the obtained precipitate is subsequently treated to obtain a doped ternary positive electrode material precursor; The calcination is to mix the doped ternary cathode material precursor and lithium hydroxide, and then perform low-temperature roasting and high-temperature calcination to obtain the doped ternary cathode material.
2. The method for directly preparing an iron-magnesium doped ternary positive electrode material from manganese purified slag according to claim 1, characterized in that: The mass ratio of the manganese purification slag to the manganese dioxide-rich substance is 1:(10-14), the concentration of the dilute sulfuric acid is 90g / L-110g / L, the liquid-solid ratio of the dilute sulfuric acid to the mixed slag is (6-9)mL:1g, the temperature of the heated leaching is 70-90°C, the leaching time is 150-180min, and the crushed particle size is 0.0374mm-0.0750mm.
3. A method for directly preparing an iron-magnesium doped ternary positive electrode material from manganese purified slag according to any one of claims 1 to 2, characterized in that: The manganese dioxide-rich substance is pyrolusite.
4. The method for directly preparing an iron-magnesium doped ternary positive electrode material from manganese purified slag according to claim 1, characterized in that: In the decalcification, the acidic condition is pH 1.0-2.0; the organic phosphate extractant is prepared by mixing P204 and sulfonated kerosene at a volume ratio of 10%-30% of P204, and then adding sodium hydroxide for saponification, wherein the saponification rate is 10%-30%, and the ratio of the organic phase to the sulfate leaching solution is (1-3):
1.
5. The method for directly preparing an iron-magnesium doped ternary positive electrode material from manganese purified slag according to claim 1, characterized in that: In the nickel-cobalt-magnesium-iron salt compounds, the nickel salt is one or a mixture of nickel sulfate, nickel chloride, nickel acetate and nickel nitrate; the cobalt salt is one or a mixture of cobalt sulfate, cobalt chloride, cobalt acetate and cobalt nitrate; the magnesium salt is one or a mixture of magnesium sulfate, magnesium chloride and magnesium nitrate; and the iron salt is one or a mixture of ferric sulfate and ferric chloride.
6. The method for directly preparing an iron-magnesium doped ternary positive electrode material from manganese purification slag according to claim 1, characterized in that: In the preparation of the precursor, the concentrated ammonia water is added to a concentration of 1 to 2 mol / L, the heating temperature is 50 to 70° C., the alkaline condition is pH 10 to 11.5, the concentration of sodium hydroxide is 1 to 1.5 mol / L, the flow rate of oxygen introduced is 1 to 5 L / min, and the coprecipitation reaction time is 30 to 60 min.
7. The method for directly preparing an iron-magnesium doped ternary positive electrode material from manganese purification slag according to claim 1, characterized in that: The subsequent treatment includes aging, washing, centrifugal separation, drying, ball milling and screening the precipitate.
8. The method for directly preparing an iron-magnesium doped ternary positive electrode material from manganese purification slag according to claim 7, characterized in that: In the subsequent treatment, the aging time is 60 to 120 minutes; the drying temperature is 100 to 105° C., and the drying time is 6 to 8 hours; the ball milling speed is 300 to 500 r / min, and the ball milling time is 3 to 6 hours; and the sieving size is 0.0374 mm to 0.0750 mm.
9. The method for directly preparing an iron-magnesium doped ternary positive electrode material from manganese purification slag according to claim 1, characterized in that: The molar ratio of the doped ternary positive electrode material precursor to lithium hydroxide is 1: (1.05-1.1), the temperature of the low-temperature calcination is 350-500° C., and the time is 2-4 hours; the temperature of the high-temperature calcination is 800-900° C., and the calcination time is 10-16 hours.
10. The method for directly preparing an iron-magnesium doped ternary positive electrode material from manganese purified slag according to claim 1, characterized in that: The ball milling speed is 300-500 r / min, and the ball milling time is 3-6 h.
Citation Information
Patent Citations
Method for regenerating ternary precursor by using nickel-cobalt-manganese slag
CN112830526A
A method for preparing ternary cathode materials using manganese-cobalt-nickel-containing waste residue
CN113611857B
Method for preparing copper-magnesium-doped lithium battery 811 positive electrode material from Xinjiang nickel-cobalt slag
CN116111075A
Processing technology for preparing ternary material by recovering cobalt-manganese waste residues
CN118084078A